Physical prototyping rationale in design student projects: an analysis based on the concept of purposeful prototyping. (8th April 2021) - Petrakis, Konstantinos; Wodehouse, Andrew; Hird, Abigail
Abstract: Prototyping constitutes a major theme of design education and an integral part of engineering design academic courses. Physical prototypes and the model building process, in particular, have been proved to boost students' creativity and resourcefulness and assist in the better evaluation of concepts. However, students' usage of prototypes has still not been explored in depth with the aim of being transformed into educational guidelines. This paper presents an investigation of students' reasoning behind prototyping activities based on the concept of Purposeful Prototyping, developed in the authors' previous work. This is performed by identifying instances of prototype use in students' design projects and by discovering which types of prototyping purposes they apply and to what extent, as well as by studying the relationships between purposes, early design stages, academic performance and project planning. The analysis of the results shows that prototyping can support students' learning objectives by acting as a project scheduling tool and highlights the contribution of early-stage prototyping in academic performance. It is also confirmed that students' limited prototyping scope prevents them from gaining prototyping's maximum benefits and that they require strategic guidelines tailored to their needs. A new, improved list of prototyping purposes is proposed based on the study's results.